2020
DOI: 10.3174/ajnr.a6862
|View full text |Cite
|
Sign up to set email alerts
|

Neurite Orientation Dispersion and Density Imaging for Assessing Acute Inflammation and Lesion Evolution in MS

Abstract: BACKGROUND AND PURPOSE: MR imaging is essential for MS diagnosis and management, yet it has limitations in assessing axonal damage and remyelination. Gadolinium-based contrast agents add value by pinpointing acute inflammation and blood-brain barrier leakage, but with drawbacks in safety and cost. Neurite orientation dispersion and density imaging (NODDI) assesses microstructural features of neurites contributing to diffusion imaging signals. This approach may resolve the components of MS pathology, overcoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…12 studies remained for the eligibility assessment; 5 studies were excluded based on the reasons shown on the PRISMA diagram ( Figure 1 ). A total of 7 studies investigating the brain microstructure in patients with MS using NODDI were included and met the inclusion/exclusion criteria for this meta-analysis [ 20 , 23 , 24 , 25 , 26 , 27 , 29 ]. A total of 202 patients with MS (mean age of 40.1 years) and 172 healthy controls (mean age of 35.1 years) were included.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…12 studies remained for the eligibility assessment; 5 studies were excluded based on the reasons shown on the PRISMA diagram ( Figure 1 ). A total of 7 studies investigating the brain microstructure in patients with MS using NODDI were included and met the inclusion/exclusion criteria for this meta-analysis [ 20 , 23 , 24 , 25 , 26 , 27 , 29 ]. A total of 202 patients with MS (mean age of 40.1 years) and 172 healthy controls (mean age of 35.1 years) were included.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 202 patients with MS (mean age of 40.1 years) and 172 healthy controls (mean age of 35.1 years) were included. The mean MS duration of all the studies was 8.3 years; however, two studies did not report disease duration [ 26 , 29 ]. There was no significant difference in the age and sex distribution between MS patients and healthy controls, with the caveat that one study did not provide information relating to the sex of participants [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations